Gender-Diverse Boards, ESG Engagement, and Accounting Conservatism: Evidence from Southeast Asia - AlKhayyal, Ahlam Mohamed; Jaafar, Aziz A. (International Review of Management and Marketing, 2026)
This study examines how board gender diversity (BGD) influences accounting conservatism (AC) and whether this relationship is moderated by firms’ Environmental, Social, and Governance (ESG) engagement in the context of Southeast Asia. Using listed firms domiciled in Malaysia, Indonesia, Singapore, and Thailand over the 2012-2022 period and applying the C-Score measure of conditional conservatism. We test the direct and interactive effect of BGD and ESG engagement on AC. Our findings reveal that the relationship between gender-diverse boards and conservative accounting is context-dependent. While Singapore exhibits a direct positive association between BGD and AC, the relationship insignificant moderator: in Malaysia, strong ESG commitment activates the latent positive effect of BGD on conservatism, whereas in Singapore, high ESG scores weaken this relationship, suggesting a potential “dark side” of ESG as a legitimacy mechanism that substitutes for prudent reporting. This study contributes to the literature by integrating gender diversity, ESG engagement, and accounting conservatism into a unified framework. It demonstrates that the governance impact of board diversity is contingent on a firm’s ethical environment and institutional setting, offering important implications for policymakers, regulators, and investors seeking to promote substantive rather than symbolic sustainability practices.